1997
DOI: 10.1007/pl00006978
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Abscisic Acid Biosynthesis and Catabolism during Dormancy Breaking in Fagus sylvatica Embryo

Abstract: At harvest, embryos of Fagus sylvatica are dormant. A cold pretreatment without medium at 30% moisture content allowed them to germinate. A comparison of the abscisic acid (ABA) content before and after the pretreatment has no significant relevance since dormancy is expressed during the culture at 23°C. During this culture, both de novo biosynthesis and conjugate hydrolysis contributed to maintain a high level of ABA in the dormant axis. The level of conjugates and the rate of hydrolysis were not modified subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 15 publications
(14 reference statements)
3
18
0
1
Order By: Relevance
“…However, when chilled seeds were returned to standard germination conditions we then observed a new and strong decrease in the ABA level to 70 pmol g À1 DW, just before chilled seeds germinated. These results were in accordance with previous observations of Le Page-Degivry et al (1997), which established that the main effect of chilling on Fagus sylvatica seeds was a strong reduction in their ABA content following their transfer from chilling conditions to standard conditions for germination. D seeds sown on nitrate presented an accelerated catabolism of ABA during the 2 days following sowing, in comparison with control D seeds.…”
Section: Release From Dormancysupporting
confidence: 95%
See 1 more Smart Citation
“…However, when chilled seeds were returned to standard germination conditions we then observed a new and strong decrease in the ABA level to 70 pmol g À1 DW, just before chilled seeds germinated. These results were in accordance with previous observations of Le Page-Degivry et al (1997), which established that the main effect of chilling on Fagus sylvatica seeds was a strong reduction in their ABA content following their transfer from chilling conditions to standard conditions for germination. D seeds sown on nitrate presented an accelerated catabolism of ABA during the 2 days following sowing, in comparison with control D seeds.…”
Section: Release From Dormancysupporting
confidence: 95%
“…The predominant pathway by which ABA is catabolized in plants is through oxidative degradation to 8¢-hydroxy-ABA with subsequent conversion to phaseic acid then reduction to dihydrophaseic acid (Walton and Li 1995). This pathway operates in the seeds of various species, for instance Fraxinus americana (Sondheimer et al 1974), Fagus sylvatica (Le Page-Degivry et al 1997) and barley (Jacobsen et al 2002), where it has been shown to be more intense in ND seeds versus D seeds. The same mechanism could operate in Cvi seeds.…”
Section: Release From Dormancymentioning
confidence: 97%
“…Moreover, ABA is necessary for dormancy maintenance during postimbibition (Le Page-Degivry and Garello 1992; Wang et al 1995;Bianco et al 1997;Le Page-Degivry et al 1997;Yoshioka et al 1998). For instance, when tobacco (Nicotiana plumbaginifolia) seeds are imbibed, there is an accumulation of ABA in dormant seeds but not in seeds that have been allowed to after-ripen.…”
Section: Introductionmentioning
confidence: 96%
“…germinate). For example, endogenous ABA levels decline in beechnut (Fagus sylvatica) embryos to the same extent regardless of dormancy status, yet [ 3 H]ABA turnover is greater in embryos subjected to a dormancy-breaking cold pretreatment than in embryos that remain dormant because of their maintenance at 23°C (Le Page-Degivry et al 1997). Increased ABA catabolism is associated with dormancy termination of seeds of yellow-cedar (Chamaecyparis nootkatensis), beechnut, Douglas fir (Pseudotsuga menziesii), and barley (Hordeum vulgare) (Le Page-Degivry et al 1997;Schmitz et al 2000Schmitz et al , 2002Corbineau et al 2002;Jacobsen et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…According to our results ABA level decreased continually in cotyledons as well as in embryonic axes during stratification and the drop of more than 50% is linked with the successful breaking the dormancy. In beech seeds the decrease in the level of ABA correlated with ABA degradation during the dormancy breaking and with the inability to synthesize ABA (Le Page-Degivry et al 1997). High ABA level in embryos inhibits the transition to germination (Rodríguez-Gacio et al 2009).…”
Section: Discussionmentioning
confidence: 99%